Study Search and the Perception of the Stakeholders of the Alumni Fakultaas Tarbiyah dan Ilmu Keguruan IAIN Padangsidimpuan - suparni (International Journal Of Humanities Education and Social Sciences (IJHESS), 2021)
One measure of the success of a program organizers education is how the program graduates can be engaged or absorbed by the jobs that are available outside the campus, received an award from the labor market and that is much better is a graduate of the can to create new jobs so that it can absorb the graduates of the other that have not worked. The quality of an educational program can also be seen from the level of satisfaction of the users (Stakeholders). The reality on the ground is the magnitude of the number of graduates is not comparable with the field work that has been available. Also the alumni of the less ably meet the demands of field of working and operation are available, or entrepreneurship. There is also a sense of disappointment of the graduate users (stakeholders) of the competence of most of the alumni. This study aims to determine the absorption field work, knowing the perception of the stakeholders of the competence of the alumni and to determine the competencies or skills that should be given to the candidates for alumni of the Faculty of Tarbiyah dan Ilmu keguruan IAIN Padangsidimpuan that can answer the needs of the field work.the results of this study show that most of the alumni have worked on a variety of sectors, however, a large part can still work in the sector in accordance with their educational background that is from the field of islamic studies or education. Most stakeholders say positive things of the competence of the alumni FTIK IAIN Psp. Competency or skills that need to be given to the candidates alumni in accordance with the needs of the field work at this time is a skill in operating a computer, not just could be but smoothly and proficiently, especially in terms of data processing, such as MS Excel, Ms-Word, Power Point and technique organizes learning online that is effective and efficient.